2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333630
|View full text |Cite
|
Sign up to set email alerts
|

Development of a portable actuated orthotic glove to facilitate gross extension of the digits for therapeutic training after stroke

Abstract: An externally actuated glove, controlled by a microprocessor, is being developed to assist finger extension in stroke survivors. The goal of this device is to allow repeated practice of specific tasks for hand therapy in a home environment. The user can control the device by three different means: voice recognition, electromyography, or manual control. These inputs can be used either independently or in combination according to the needs of the user. Both position and force feedback are available for control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…One limitation of devices with palmar structure is their inability for the user to perform palmar or pincer grasps, two functionally important motor control strategies, in real (not virtual reality) environments. Exoskeleton systems for the hand can have independent degrees of freedom (DOF) for each finger as in [12,13] or they can lump the index through the small finger together into one functional unit with 1-DOF [7,9,10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of devices with palmar structure is their inability for the user to perform palmar or pincer grasps, two functionally important motor control strategies, in real (not virtual reality) environments. Exoskeleton systems for the hand can have independent degrees of freedom (DOF) for each finger as in [12,13] or they can lump the index through the small finger together into one functional unit with 1-DOF [7,9,10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…While this body of work has shown that intuitive control is indeed possible, it has also highlighted numerous challenges. For example, EMG signals are inherently abnormal in hemiparesis and distorted by spasticity and fatigue [8], [9]. If signal patterns drift or change between training and deployment, the control method has no way of coping without new calibration or training data.…”
mentioning
confidence: 99%
“…However, this device requires the subject to use shoulder and elbow movement to assist with finger extension, which decreases the ability for normal movement kinematics in reach and grasp task training. This device has been extended to a motorized device controlled with voice, electromyography or manual input [15]. However, this change makes the device no longer passive, and the increased complexity and weight may affect arm transport and limit potential home use.…”
mentioning
confidence: 99%